Literatur Review : Homesickness pada Mahasiswa Tahun Pertama - Alifia Putri Fadilah Sati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This literature review aims to provide a comprehensive understanding of homesickness, or homesickness, particularly experienced by first-year college students. The transition from home life to a new campus environment often causes psychological stress, especially for those living away from family for the first time. One form of this stress is homesickness, which can impact students' mental, social, and academic well-being. This study used a literature review method, a data collection and analysis technique that involves identifying, evaluating, and synthesizing the results of previous research. In this study, the authors reviewed 15 scientific articles that directly discussed homesickness, as well as one additional article that discussed the literature review method. The results indicate that homesickness is a complex emotional condition, characterized by feelings of sadness, loneliness, and impaired concentration that arise due to separation from a familiar home environment. Factors contributing to homesickness include a lack of social support, strong emotional attachment to family, and an inability to adapt to a new environment. The forms of homesickness can vary, from mild to disruptive to daily functioning. Symptoms can include physical complaints, sleep problems, and decreased motivation. Several prevention and management strategies that can be implemented include strengthening social support, developing coping skills, and campus-based psychological interventions. By understanding the characteristics of homesickness, it is hoped that campuses and students can take proactive steps to address it.